Assessment of balance in mild and moderate stages of Alzheimer's disease: implications on falls and functional capacity - Eliane Mayumi Kato-Narita; Ricardo Nitrini; Marcia Radanovic (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To analyze the correlation between balance, falls and loss of functional capacity in mild and moderate Alzheimer's disease(AD). METHOD: 40 subjects without cognitive impairment (control group) and 48 AD patients (25 mild, 23 moderate) were evaluated with the Berg Balance Scale (BBS) and the Disability Assessment for Dementia (DAD). Subjects answered a questionnaire about falls occurrence in the last twelve months. RESULTS: Moderate AD patients showed poorer balance (p=0.001) and functional capacity (p <0.0001) and it was observed a correlation between falls and balance (r= -0.613; p=0.045). CONCLUSION: There is a decline of balance related to AD which is a factor associated to the occurrence of falls, albeit not the most relevant one. The loss of functional capacity is associated with the disease's progress but not to a higher occurrence of falls. The balance impairment did not correlate with functional decline in AD patients.